Effects of pentoxifylline and metformin combination therapy compared to metformin alone in infertile women with symptomatic endometrioma - Lasker, Nastaran; Banu, Jesmine; Munira, S. M.; Al Tarique, Mostafa M.; Anwary, Shahin Ara; Ghosh, Tandra; Sultana, Sharmin; Laila, Rawnok; Akter, Asma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometriosis, a chronic inflammatory disease, significantly affects reproductive health and fertility in women. This study compares the efficacy of pentoxifylline plus metformin versus metformin alone in treating symptomatic endometrioma in infertile women. Methods: This randomized controlled trial was conducted at the department of reproductive endocrinology and infertility, BSMMU, Dhaka, from July 2022 to June 2023, involving 51 women. Participants were randomly allocated into two groups: pentoxifylline plus metformin (n=25) and metformin alone (n=26). Baseline and post-treatment evaluations included the size of endometrioma, pain scores using the visual analogue scale (VAS), and serum interleukin-6 (IL-6) levels. Data analysis focused on comparing treatment outcomes between the two groups. Result: At baseline, both groups were comparable in terms of sociodemographic characteristics, BMI, and type and duration of infertility. Post-treatment, the pentoxifylline plus metformin group showed significant reductions in endometrioma size (2.23±0.97 cm), VAS score (2.73±1.21), and IL-6 levels, all with p<0.001s. In contrast, the metformin alone group exhibited a significant reduction in endometrioma size (3.12±1.42 cm, p=0.003s) and VAS score (3.48±1.89, p<0.001s), but not in IL-6 levels (p=0.505ns). Pregnancy rates were 8.0% in the pentoxifylline plus metformin group and 3.85% in the metformin alone group (p=0.610ns). Side effects were minimal and comparable between the two groups. Conclusions: Pentoxifylline plus metformin demonstrated superior efficacy in reducing endometrioma size, pain scores, and IL-6 levels compared to metformin alone. However, no significant differences were observed in pregnancy rates or side effects. These findings indicate that the combination therapy could offer greater benefits in managing endometrioma size and pain, although further research is required to evaluate its impact on fertility outcomes in endometriosis patients.